THU0238 Ultrasonographic evaluation of distal patellar enthesis in patients affected by entheropatic spondiloarthritis. (12th June 2018) - Batticciotto, A.; Prato, G.; Antivalle, M.; Ditto, M.C.; Agosti, M.; Cumbo, E.; Talotta, R.; Atzeni, F.; Sarzi-Puttini, P.
Abstract : Background: Enteropathic arthritis (EA) belongs to the spondyloarthritis (SpA) spectrum of diseases and occurs in patients affected by inflammatory bowel diseases (IBD). Several works demonstrated that ultrasonography (US) is a feasible, reliable and easily accessible tool for detecting chronic and active entheseal abnormalities even in a subclinical contest in SpA patients. 1, 2 Objectives: To evaluate the prevalence of US entheseal involvement of the distal insertion of patellar ligament in patients affected by EA. Methods: Twenty-two consecutive AE patients (12 with Crohn's disease and 10 with ulcerative colitis; 8 females and 14 males; mean age 44.7 years, range 18–72 years; mean AE duration 10.1 years range 4–21 years) and 18 healthy age- and gender-matched controls (8 females and 10 males; mean age 48 years, range 24–68 years) underwent an US examination (ESAOTE MyLAB 70 6–18 MHz linear array transducer) according with the validated Madrid Sonographic Enthesis Index (MASEI). Clinical and clinimetric variables were assessed in both groups according with daily clinical practice. Results: Focusing on the 44 distal patellar entheses we identified a higher prevalence of all the elementary lesion analysed. In 34 entheses we identify a dishomogeneous echostructure (77.3% vs 33.3%; p=0.0001), in 38 structural thickness (86.4% vs 66.7%; p=0.03), in 16 power Doppler positivity (36.3% vs 16.7%; p=0.04), in 17 presence of calcifications (38.6% vs 16.7%; p=0.03) and in 8 entheses the presence of erosions (18.8% vs 0%; p=0.007). In the 45% of the examined patients we detected a simultaneous presence of dishomogeneous echostructure, structural thickness and power Doppler positivity suggestive for US active enthesitis at the level of the same enthesis. Conclusions: US detectable signs of enthesopathy and enthesitis are very frequent in EA patients even when we analyse the distal enthesis of the patellar ligament alone. Further studies involving a larger number of patients are needed to confirm these preliminary data. References: [1] Atzeni F, Defendenti C, Ditto MC, et al. "Rheumatic manifestations in inflammatory bowel disease". Autoimmun Rev. 2014Jan;13(1):20–3. [2] Wakefield RJ, Green MJ, Marzo-Ortega H, et al. Should oligoarthritis be reclassified? Ultrasound reveals a high prevalence of subclinical disease. Ann Rheum Dis2004;63(4):382–5. Disclosure of Interest: None declared